Barrier Height, Ideality Factor and Role of Inhomogeneities at the AlGaN/GaN Interface in GaN Nanowire Wrap-Gate Transistor - Siva Pratap Reddy Mallem; Peddathimula Puneetha; Yeojin Choi; Seung Mun Baek; Dong-Yeon Lee; Ki-Sik Im; Sung Jin An (Nanomaterials, 2023)
It is essential to understand the barrier height, ideality factor, and role of inhomogeneities at the metal/semiconductor interfaces in nanowires for the development of next generation nanoscale devices. Here, we investigate the drain current (Ids)–gate voltage (Vgs) characteristics of GaN nanowire wrap-gate transistors (WGTs) for various gate potentials in the wide temperature range of 130–310 K. An anomalous reduction in the experimental barrier height and rise in the ideality factor with reducing the temperature have been perceived. It is noteworthy that the variations in barrier height and ideality factor are attributed to the spatial barrier inhomogeneities at the AlGaN/GaN interface in the GaN nanowire WGTs by assuming a double Gaussian distribution of barrier heights at 310–190 K (distribution 1) and 190–130 K (distribution 2). The standard deviation for distribution 2 is lower than that of distribution 1, which suggests that distribution 2 reflects more homogeneity at the AlGaN/GaN interface in the transistor’s source/drain regions than distribution 1.